2019
DOI: 10.3897/phytokeys.134.38287
|View full text |Cite
|
Sign up to set email alerts
|

Sedum lipingense (Crassulaceae) identifying a new stonecrop species in SE Guizhou, China, based on morphological and molecular evidence

Abstract: We describe and illustrate Sedum lipingense (Crassulaceae), a new species of stonecrop found in the limestone areas of SE Guizhou, China. Based on the presence of adaxially gibbous carpels and follicles, this taxon belongs to sect. Sedum S.H. Fu. The new species superficially resembles S. subtile Miquel and S. bulbiferum Makino but differs from these two taxa in its development of a basal leaf rosette during florescence. The nrDNA internal transcribed spacer (ITS) sequences also support the claim that this pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“… Sedum might not be monophyletic. This result is consistent with previous studies ( Nikulin et al 2016 ; Zhang et al 2019 ; Messerschmid et al 2020 ).…”
Section: Results and Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“… Sedum might not be monophyletic. This result is consistent with previous studies ( Nikulin et al 2016 ; Zhang et al 2019 ; Messerschmid et al 2020 ).…”
Section: Results and Discussionsupporting
confidence: 94%
“…During the past 20 years, about seventeen Sedum species have been newly described from China, including S. hoi X.F.Jin & B.Y.Ding ( Wang et al 2005 ), S. plumbizincicola X.H.Guo & S.B.Zhou ( Wu et al 2012 ), S. fanjingshanense C.D.Yang & X.Yu Wang ( Yang et al 2012 ), S. kuntsunianum X.F.Jin, S.H.Jin & B.Y.Ding ( Jin et al 2013 ), S. tarokoense H.W.Lin & J.C.Wang ( Lu et al 2013 ), S. spiralifolium D.Q.Wang, D.M.Xie & L.Q.Huang ( Xie et al 2014 ), S. peltatum M.L.Chen & X.H.Cao ( Chen et al 2017 ), S. kwanwuense H.W.Lin, J.C.Wang & C.T.Lu and S. taiwanalpinum H.W.Lin, J.C.Wang & C.T.Lu ( Lu et al 2019 ), S. ichangense Y.B.Wang ( Wang and Xiong 2019 ), S. lipingense R.B.Zhang, D.Tan & R.X.Wei ( Zhang et al 2019 ), S. nanlingense Yan Liu & C.Y.Zou ( Zou et al 2020 ), S. cirenianum S.S.Ying, S. shaoakouense S.S.Ying and S. shengkuangense S.S.Ying ( Ying 2022a ), and S. parviflorum S.S.Ying and S. tachingshuianum S.S.Ying ( Ying 2022b ).…”
Section: Introductionmentioning
confidence: 99%
“…Among the five endemic Korean plants used in this study, we found that the SMM extract had antitumor potential by inducing apoptosis and inhibiting invasion of human ovarian cancer cells. SMM, termed as "aegi-gilincho" in Korea, is an endemic plant species belonging to the Sedum genus in the Crassulaceae family [27]. Approximately 121 Sedum species (91 endemic) occur in Asia.…”
Section: Discussionmentioning
confidence: 99%